Computer Forensics Data Recovery Software: A Comparative Study (International Journal of Innovative Research in Computer Science & Technology, 2022)
With the advancement of the information  technology, computer has become more important for the  people. Computer not only stores data but also increase the  channels of storing data in digital devices like pen drive,  hard disk, memory card. However, problem with these  digital devices is that if data has lost it is very difficult to  recover; so many researchers do research on it and  suggested the method of data recovery. The term data refers  to the combination of numbers or words, images, audio or  video files or even a software program. Data restore is the  procedure of recovery of information from media that is  either corrupted or damaged physically. The data recovery  software extracts the data that requires serving as an  evidence from personal computers and digital devices in  criminal cases that involve frauds, murder, corruption,  money laundering, assault, smuggling, email scams, digital  abuse, matrimonial frauds and much more. Here in this  study, we combine probably all data recovery software and  we will conclude that the best data recovery software in  forensic sound manner. This study will help in future study  to understand the overview of computer forensics data  recovery software.
Keywords: Acquisition; Computer Forensic; Data Recovery; DataForensic; Digital Devices